2022
DOI: 10.1177/02662426221097910
|View full text |Cite
|
Sign up to set email alerts
|

Individual religious affiliation, religiosity and entrepreneurial intentions among students in four countries

Abstract: This article explores religion and religiosity in the field of entrepreneurship. Based on an original, international dataset of 740 students, we examine the impact of individual religious affiliation (Protestant, Catholic or Muslim) or non-affiliation (Agnostic/Atheist) on entrepreneurial intentions. We further examine the influence of individual religiosity (beyond mere religious affiliation) on entrepreneurial intentions, offering new insights as to the role religion and religiosity play in entrepreneurship.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 76 publications
0
21
0
8
Order By: Relevance
“…Henley (2017) argued that religion has a range of cultural and institutional influences that impact entrepreneurial activity. Giacomin et al (2022) explored religion and religiosity in the field of entrepreneurship and supported the notion that religion matters in enhancing EIs. Musallam and Kamarudin (2021) provided a systematic review of contributions related to religiosity and entrepreneurship and suggested potential empirical and conceptual research by highlighting religiosity as a driving force for entrepreneurial activity.…”
Section: Religiosity Attitude Towards Entrepreneurship and Entreprene...mentioning
confidence: 85%
See 1 more Smart Citation
“…Henley (2017) argued that religion has a range of cultural and institutional influences that impact entrepreneurial activity. Giacomin et al (2022) explored religion and religiosity in the field of entrepreneurship and supported the notion that religion matters in enhancing EIs. Musallam and Kamarudin (2021) provided a systematic review of contributions related to religiosity and entrepreneurship and suggested potential empirical and conceptual research by highlighting religiosity as a driving force for entrepreneurial activity.…”
Section: Religiosity Attitude Towards Entrepreneurship and Entreprene...mentioning
confidence: 85%
“…Henley (2017) argued that religion has a range of cultural and institutional influences that impact entrepreneurial activity. Giacomin et al . (2022) explored religion and religiosity in the field of entrepreneurship and supported the notion that religion matters in enhancing EIs.…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…In this article, I investigated the role of religiosity on goal-specific entrepreneurial intention, with entrepreneurial self-efficacy and entrepreneurial motivation as mediating variables. Giacomin et al (2022) stated that religion creates a framework of implicit and explicit values defining desirable and undesirable actions. Distinctly, religion is a fundamental variable that plays a significant role in people's lives, and it promotes certain types of individual behaviour, career choices and intentions to be an entrepreneur.…”
Section: Religiosity Entrepreneurial Self-efficacy and Entrepreneuria...mentioning
confidence: 99%
“…Islam is a religion that promotes entrepreneurship, as the hadith narrated by Ibn Majah, Hakim and Darruqutni from Abdullah bin Umar says that Muhammad SAW said, “an honest and trustworthy Muslim trader will be together with the Prophet, the honest, and the martyrs on the Day of Judgment” (Adi and Adawiyah, 2018). Furthermore, Giacomin et al (2022) asserted that affiliation to a particular religion, including Islam, affects the entrepreneurial intention of a Muslim.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The factors that influence entrepreneurship focus on individual, social, and policy aspects. Individual factors include education, risk appetite, occupation experience, and family background ( Halvarsson et al, 2018 ; Duleep et al, 2022 ; Giacomin et al, 2022 ). Social factors refer to migration and mobility ( Lee and Eesley, 2018 ; Duleep et al, 2022 ), the internet economy and digital finance ( Cumming and Johan, 2010 ; Liu et al, 2022 ), and the business environment ( Wu and Lin, 2021 ).…”
Section: Introductionmentioning
confidence: 99%